Mechanisms for the retrieval of meanings in urban renewal - khales Hasan al-ashaab; Maysoun mouhy hlal (Iraqi Journal of Architecture and Planning, 2009)
The Urban strategies organized t}re materialism and formalism characteristicsof the urban fabric limiting types and distribution the activities. And the nature oftheuse despite the difference of nature ofthese strategies but they work away to:l - Limitate the size of the city and its expansion, for the aim ol decrease the costs ofsupply the services levels, to improving the administrative systems, and preventthe social disintegration by protecting the environmental and social characteristicsto it.2- To recognize the land use to ensure the environmental and functional ability, tocontrol the traffic and the main movement and its branchs. Commonly, the urbanstrategy declares on itself by its aims behind groups lrom the included and thedeclared values which some of them related with the urban structure in accordancewith the past, the researching problem directed to the following axes:I - How we can find a sensitive scale for prediction the effect of limiting Part throughthe whole structure syntactically and morphologically, to carry this part a socialcharacteristics and the meanings system according to pre-deliberatedconsideration by urban renewal plan.2- Non-existence of standard machinery to restitute the meanings system ofthe urbanspace from the society to the space and vise-versa, to use it in urban renewalprocesses.To solve the researching problem, the research adopt (The Space Syntax BiasesTheory) as a main method to limitation the relations between the syntactical spacebiases of renewal area with the space characteristics to the whole structure build, thebenefit from this theory as a mechanisms to restitute the urban space meaningssystem, and use it in the urban renewal ofa seleited area in Baghdad, it is (Urbanfabric of risafa) as a study statement for attainment the research results , ( It is amachineries to restitute the urban space meanings system).